Assessment of enthesitis in patients with psoriasis: Relationships with clinical features, screening questionnaries results, and quality of life: An ultrasound study - Dulović Dragan; Rančić Nemanja; Božić Ksenija; Stamatović Ratko; Mijušković Željko; Pešić Jasna; Kremić Zorana; Vojinović Radiša; Petronijević Milan (Vojnosanitetski Pregled)
Background/Aim. Often asymptomatic, enthesitis can be an integral feature of the wide clinical spectrum in psoriasis as well as an early sign of development of psoriatic arthritis (PsA). It may be difficult to clinically recognize enthesitis in patients with psoriasis or distinguish it from other causes of extraarticular pain. Ultrasound (US) expanding use with the development of accurate assessments through standardized US algorithms as the Glasgow Ultrasound Enthesis Scoring System (GUESS) and the Madrid Sonographic Enthesitis Index Scoring System (MASEI) scores made the US the dominant imaging technique in diagnosing enthesitis. The aims of this study were to establish the prevalence of US signs of en-thesitis, compare it with screening questionnaires results, and estimate possible connections of US verified enthesitis with quality of life (QOL) of patients with psoriasis without PsA diagnosis. Methods. A cross-sectional study was performed on 67 patients with psoriasis who were without systemic therapy. The clinical presence of enthesitis was examined by an experienced rheumatologist, and systemic inflammation was estimated through serum level of C-reactive protein (CRP). The Psoriasis Area Severity Index (PASI) and Body Surface Area- Psoriasis (BSA-PsO) were calculated by a dermatologist. Visual analogue scale (VAS) for pain, screening questionnaires – the Toronto Psoriatic Arthritis Screening (ToPAS), Psoriasis Ep-idemiology Screening Tool (PEST), Psoriatic Arthritis Screening and Evaluation (PASE), Early Psoriatic Arthritis Screening Questionnaire (EARP), and Psoriasis and Arthrosis Screening Questionnaire (PASQ) – were filled by patients. GUESS and MASEI scores were determined by US. The QOL was estimated by the Dermatology Life Quality Index (DLQI). Results. The presence of clinical enthesitis was recorded in 8.7% of patients. According to US signs of enthesitis using GUESS and MASEI scores, only 7% and 2% of patients, respectively, had no sign of enthesitis. Duration of psoriasis and age of subjects were in a significant correlation with GUESS and MASEI scores, while systemic inflammation, V AS v alue, PASI, and BSA-PsO scores were not. GUESS and MASEI scores significantly correlated with scores of all screening questionnaires as well as with DLQI. Conclusion. US can detect subclinical enthesitis better than clinical examination and widely used screening questionnaires, even though the correlations between MASEI and/or GUESS scores and results of screening questionnaires were positive. US examination is important in the multidisciplinary approach in diagnosing and managing psoriasis.